2010
DOI: 10.1609/icaps.v20i1.13429
|View full text |Cite
|
Sign up to set email alerts
|

Waking Up a Sleeping Rabbit: On Natural-Language Sentence Generation with FF

Abstract: We present a planning domain that encodes the problem of generating natural language sentences. This domain has a number of features that provoke fairly unusual behavior in planners. In particular, hitherto no existing automated planner was sufficiently effective to be of practical value in this application. We analyze in detail the reasons for ineffectiveness in FF, resulting in a few minor implementation fixes in FF's preprocessor, and in a basic reconfiguration of its search options. The performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Another possible future direction is applying our approach to other domains, such as natural language generation. A connection between natural language generation and planning has been previously established (e.g., Koller and Hoffmann 2010). Grammars are explored widely for generating natural language and thus our approach should work almost out of the box, allowing for focused exploration of possible sentences.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Another possible future direction is applying our approach to other domains, such as natural language generation. A connection between natural language generation and planning has been previously established (e.g., Koller and Hoffmann 2010). Grammars are explored widely for generating natural language and thus our approach should work almost out of the box, allowing for focused exploration of possible sentences.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Hence, planning techniques at the grounded level are limited to planning tasks where that blow-up is not prohibitive. It has been frequently observed that this excludes a variety of applications (e. g. [11,16,17,8,19]).…”
Section: Introductionmentioning
confidence: 99%
“…A drawback of this approach is that the size of the grounded task representation may -in the worst casegrow exponentially with regard to action and predicate arity. But in many real world problems both can be quite large and the problems therefore quickly become infeasible to solve using grounded representations (see e. g. (Hoffmann et al 2006;Koller and Hoffmann 2010;Koller and Petrick 2011;Haslum 2011;Matloob and Soutchanski 2016)). Lifted planning does not rely on a grounded task representation and instead works directly on the lifted planning models.…”
Section: Introductionmentioning
confidence: 99%